PENGARUH PEMBERIAN KAPSUL KELOR TERHADAP PRODUKSI ASI - Yuliati Shoffiyah; Achmad Farich; Dainty Maternity; Ike Ate Yuviska (JKM (Jurnal Kebidanan Malahayati), 2021)
ABSTRACT : THE EFFECT OF GIVING MORINGA CAPSULES ON BREAST MILK PRODUCTIONBackground In Indonesia, the proision of breastfeeding eclusiely for si months just reached 30.2% case is still far from the target that 80% regard it in because of lack of awareness of society in encouraging an increase in the proision of breastfeeding eclusiely , lack of knowledge of mothers , families and communities about the importance of breastfeeding eclusiely . The purpose of this study was to determine the effect of morngaoliefera leaf capsules on breast milk production in the working area puskesmas of Gedung Sari Lampung entral Health enter in 2019.MethodsThis type of uantitatie research with a research design using a pre experimental approach with a pretest and post test with control group design . Samples of all nursing mothers were 40 people. The population of breastfeeding mothers is 79 people. 20 people as a group eperiment and 20 people as a group control with the techniue of sampling purposive sampling .Anilsa the data to test T-test independent.Results of the study is to show the aeragefreuency before administration of the capsule leaes of oringa to the production of breast milk in the region work PuskesmasGedung Sari entral Lampung in 2019 ie 26.50 , the aeragefreuency after administration of the capsule leaes of oringa to the production of breast milk in the region work Puskesmasuilding Sari Lampung The middle of 2019 is 80.50 , and there is an influence of giingoringa leaf capsules to the production of breast milk in the working area of the Sari Lampung entral Health enter in 2019 . ConclusionT test results obtained p value 0,000 <α (0 , 05 there is an effect of consumption of Moringa leaf capsules on milk production).  Suggestions for the public are expected that mothers want to consume Moringa leaf capsules in accordance with the recommendations because Moringa capsules can increase milk production.eKeywords   : Moringa leaf capsules giving, Production ASI Abstrak  Latar Belakang Di Indonesia pemberian ASI eksklusifselamaenambulanbarumencapai 30,2% halinimasihjauhdari target yaitu 80% halini di karenakan rendahnya kesadaran masyarakat dalam mendorong peningkatan pemberian ASI eksklusif, kurangnya pengetahuan ibu, keluarga serta masyarakat tentang pentingnya ASI eksklusif.Tujuan dari penelitian ini adalah mengetahui pengaruh pemberian kapsul daun kelor terhadap produksi ASI di wilayah kerja Puskesmas Gedung Sari Lampung Tengah Tahun 2019. Metode Jenis penelitian kuantitatif dengan rancangan penelitian menggunakan pendekatan pre experimental dengan rancangan pretest dan post test with control group. Populasi ibu menyusui sebanyak 79 orang. Sampel seluruh ibu menyusui sebanyak 40 orang. 20 orang sebagai kelompok eksperimen dan 20 orang sebagai kelompok kontrol dengan teknik sampling purposive sampling. Analisa data dengan uji T-test independent.Hasil penelitian ini menunjukan rata-rata  frekuensi sebelum pemberian kapsul daun kelor terhadap produksi ASI di wilayah kerja Puskesmas Gedung Sari Lampung Tengah Tahun 2019 Tahun 2019 Yaitu 26.50, rata-rata frekuensi sesudah pemberian kapsul daun kelor terhadap produksi ASI di wilayah kerja Puskesmas Gedung Sari Lampung Tengah Tahun 2019 Yaitu 80.50, serta ada pengaruh pemberian pemberian kapsul daun kelor terhadap produksi ASI di wilayah kerja Puskesmas Gedung Sari Lampung Tengah Tahun 2019 .Kesimpulan ada pengaruh konsumsi kapsul daun kelor terhadap produksi ASI.Saran untuk masyarakat diharapkan para ibu mau mengkonsumsi kapsul daun kelor sesuai dengan anjuran karena kapsul kelor dapat meningkatkan produksi ASI.Kata kunci           : Pemberian Kapsul Daun Kelor, Produksi ASI